Cochlear Implantation in Vestibular Schwannoma: A Systematic Literature Review - Tadokoro, Kent; Bartindale, Matthew Robert; El-Kouri, Nadeem; Moore, Dennis; Britt, Christopher; Kircher, Matthew (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Ipsilateral cochlear implantation (CI) in vestibular schwannoma (VS) has been an emerging trend over the last two decades. We conducted the first systematic review of hearing outcomes comparing neurofibromatosis 2 (NF2) and sporadic VS undergoing CI. A comparison of the two populations and predictor of outcome was assessed. This is an update to a previously presented study.Data Sources Systemic data searches were performed in PubMed NCBI and Scopus by an academic librarian. No restrictions based on the year of publication were used.Study Selection Studies were selected if patients had a diagnosis of NF2 and a CI placed in the affected side with reports of hearing outcome. Two independent reviewers screened each abstract and full-text article.Data Extraction Studies were extracted at the patient level, and the assessment of quality and bias was evaluated according to the National Institutes of Health Quality Assessment Tool.Main Outcome Measures Outcome predictors were determined by using the chi-square test and Student's t-test.Results Overall, most CI recipients functioned in the high-to-intermediate performer category for both sporadic and NF2-related VS. Median AzBio (Arizona Biomedical Institute Sentence Test) was 72% (interquartile range [IQR]: 50) in NF2 patients and 70% (IQR: 7.25) in sporadic patients. Larger tumor size predicted a poorer final audiometric outcome.Conclusions Categorization of hearing outcome into superior performance and inferior performance based on sentence recognition revealed a generally good hearing outcome regardless of treatment or patient population. Select patients with sporadic and NF2 VS may benefit from CI.
Keywords: vestibular schwannoma; acoustic neuroma; neurofibromatosis type 2; cochlear implant; hearing conservation surgery; hearing rehabilitation; stereotactic radiosurgery